ICT ON TEACHING ENGLISH LANGUAGE AND LITERATURE - Muh. Takdir (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2020)
A gale of change is blowing in the pedagogy of English Language Teaching (ELT) ICT has initiated new possibilities into classroom. The role of the teacher, the nature and the context of learning, as well as the function and relative importance of course cotent have all been challenged and redefined. This research paper aims at sharing practical experiments wth ICT in teaching English language and literature. It deals with the pragmatic aspects of using ICT with the student community of business management and humanities. The extensive use of web 2.0. components, internet, blogs, e-groups, SMSs, emails. Socializing portals, e-dictionaries, e-encyclopedia, power point presentation, webcasting, and audio-video, as teaching tools have been mad in the classroom. The student community was motivated to make use of cyber cafes and GPRS mobiles to interact with the teacher. The paper is divided in two parts. in the first part of the paper deals with the experiments carried out to develop Business English skills. The second part is dedicated in teaching literature, while the third part deals with general inferences of these experiments, its limitations and opportunities